Scientific production at the Cerebrospinal Fluid Central Laboratory - Alejandro Ramos Robledo; Christian Meijides Mejías; Alberto Juan Dorta Contreras; José Felix Villanueva Baquedano (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2021)
Background: The Central Cerebrospinal Fluid Laboratory is almost 17 years old, as an entity of science and technological innovation that is distinguished by its prolific scientific production. Objective: to characterize the scientific production of researchers and assistant students in the Central Laboratory of Cerebrospinal Fluid. Methods: bibliometric, descriptive study of the scientific publications of the Cerebrospinal Fluid Central Laboratory, attached to the Miguel Enríquez Faculty of Medical Sciences, Havana University of Medical Sciences. The scientific production from April 2004 to February 2020 was analyzed, according to the Google Scholar, Scopus and PubMed databases. The variables reported by Publish or perish version 7 advanced were obtained, such as h indices and their variants. The network analysis was also done by VOSviewer, version 1.6.13. Results: a total of 426 articles were published. The founding researcher showed an h-index (given by Google Scholar) of 20, which decreased as other authors joined the group. There were two authors with the same h-index, but with a higher g-index, that is, they accumulated a greater number of citations for the same number of works included in the index, and the h and g scope was inversely proportional to the years of experience, and therefore, to the number of publications of authors with index h = 1 or higher. Conclusion: Scientific production has been extensive, sustainable in number and shows what the team has achieved with systematic impact work.